Efektivitas Ekstrak Kaempferia Galanga Terhadap Proses Penyembuhan Luka - Renni Yuniati; Farah Chilwa Hidayati; Muhammad Auzinal Haq; Muhammad Ahda Sabila (Jurnal Impresi Indonesia, 2025)
Wound healing is a complex biological process that involves various stages of tissue regeneration. In the world of traditional medicine, Kaempferia galanga is widely known for its content of active compounds that have anti-inflammatory, antimicrobial, and antioxidant properties. This study aims to systematically review the adjuvant therapeutic efficacy of Kaempferia galanga rhizome extract in accelerating wound healing based on published experimental studies. This research method uses a systematic literature review approach by examining articles from national and international scientific databases over the past ten years. The results of the study show that the administration of Kaempferia galanga extract can increase re-epithelialization, reduce inflammatory response, and accelerate the formation of granulated tissue. Overall, rhizome-based adjuvant therapy Kaempferia galanga has the potential to be an alternative in the development of more natural and safe wound-healing agents. The conclusions of this study emphasize the importance of further exploration through clinical trials to ensure the effectiveness and safety of its long-term use in medical practice.